The Phenomenon of Retired Employees Who Are Re-Employed to Fulfill Their Tax Obligations - Salwa Marcella Avira; Puteri Tiara Machmud; Zahid Fikru Ar Royyan; Galuh Tresna Murti (Jurnal Riset Perpajakan: Amnesty, 2023)
This research explores the phenomenon of retired employees being re-employed to fulfill their tax obligations, especially in relation to PPh Article 21 which applies to casual employees and retirees. Retirement is a period that requires special attention in the context of taxation. This research uses descriptive qualitative research methods to understand and describe this phenomenon. Indonesia implements a Self Assessment System in its tax system, which gives full responsibility to taxpayers in calculating and paying taxes. In the context of withholding, depositing and reporting income tax article 26 which is related to work, services and activities of individuals, the Director General of Taxes Regulation number PER-16/PJ/2016 regulates the technical guidelines. This research takes secondary data from various sources, including literature and applicable tax regulations. The research results provide insight into the calculation of PPh Article 21 for permanent employees and periodic pension recipients. This calculation involves various aspects, including the tax period, recalculation, PTKP, and the tax withholding process. This research aims to provide a better understanding of the challenges faced by retired employees who are reemployed in the context of taxation in Indonesia.